Plant Protein and Proteome Altlas--Integrated Omics Analyses of Plants under Abiotic Stresses - Li, Ling (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Integrative omics of plants in response to stress conditions play more crucial roles in the post-genomic era. High-quality genomic data provide more deeper understanding of how plants to survive under environmental stresses. This book is focused on concluding the recent progress in the Protein and Proteome Atlas in plants under different stresses. It covers various aspects of plant protein ranging from agricultural proteomics, structure and function of proteins, and approaches for protein identification and quantification.